2019
DOI: 10.1002/prot.25682
|View full text |Cite
|
Sign up to set email alerts
|

Putative structural rearrangements associated with the interaction of macrocyclic inhibitors with norovirus 3CL protease

Abstract: Human noroviruses are the primary cause of outbreaks of acute gastroenteritis worldwide. The problem is further compounded by the current lack of norovirus‐specific antivirals or vaccines. Noroviruses have a single‐stranded, positive sense 7 to 8 kb RNA genome which encodes a polyprotein precursor that is processed by a virus‐encoded 3C‐like cysteine protease (NV 3CLpro) to generate at least six mature nonstructural proteins. Processing of the polyprotein is essential for virus replication, consequently, NV 3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(100 reference statements)
2
7
0
Order By: Relevance
“…NV 3CLpro invariably shows a stronger preference for a P 2 Cha versus a P 2 Leu; , however, compounds 5h – 6h display comparatively lower potency. In this instance, gem -dimethyl substitution is inimical to both potency and permeability, possibly arising from subtle conformational effects . Diminished potency was also observed with gem -dimethyl substituted compounds one carbon shorter (Table ), suggesting that the conformational constraints imposed by the gem -dimethyl substitution impact binding adversely.…”
Section: Resultssupporting
confidence: 76%
“…NV 3CLpro invariably shows a stronger preference for a P 2 Cha versus a P 2 Leu; , however, compounds 5h – 6h display comparatively lower potency. In this instance, gem -dimethyl substitution is inimical to both potency and permeability, possibly arising from subtle conformational effects . Diminished potency was also observed with gem -dimethyl substituted compounds one carbon shorter (Table ), suggesting that the conformational constraints imposed by the gem -dimethyl substitution impact binding adversely.…”
Section: Resultssupporting
confidence: 76%
“…In general, inhibitors with the aldehyde warhead and Leu or a cyclohexylalanine at the P2 position exhibited decent inhibitory activities. The binding of the macrocyclic inhibitors was facilitated by the hydrogen bonds that also existed in the substrate binding, including the ones between the inhibitor backbone and Gln110, Ala158, Ala160, the ones between the P1 glutamic acid sidechain and Thr134, and His157 [97] (Figure 5D).…”
Section: Macrocyclic Inhibitorsmentioning
confidence: 99%
“…The MM-GBSA interaction energies revealed some important key hotspot amino acid residues for all these drugs. Among these hotspot residues, His41 was conserved among several viruses, including SARS-CoV-2 3CL pro (PDB: 6LU7) [143], SARS-CoV 3CL pro (PDB: 3TNT) [37], and MERS-CoV 3CL pro (PDB: 5WKK) [189] and HCV (PDB: 3M5L) [190].…”
Section: Molecular Modeling Conducted On Sars-cov-2 M Pro / 3cl Promentioning
confidence: 99%
“…By using AutoDock 4.2 software, Gurung and co-workers [191] performed a molecular docking study of some antiviral phytochemicals to identify effective SARS-CoV-2 M pro inhibitors. The sequence analysis revealed that the SARS-CoV-2 3CL pro (PDB: 6LU7) [143] showed 96.08% and 50.65% structural similarity with SARS-CoV 3CL pro (PDB: 3TNT) [37] and MERS-CoV 3CL pro [189]. The superimposition also displayed that SARS-CoV-2 3CL pro had a minute variation with SARS-CoV 3CL pro (RMSD ¼ 0.517 Å ) and MERS-CoV 3CL pro (RMSD ¼ 0.817 Å ).…”
Section: Molecular Modeling Conducted On Sars-cov-2 M Pro / 3cl Promentioning
confidence: 99%